Implementing Service Science Perspective with Adapting SOP as a Growth Strategy to Expand Market B2B in F&B Sector in Bandung - Winda Lestari, Karin; Novani, Santi (Journal of World Science, 2023)
Law of the Republic of Indonesia No. 18 of 2008 concerning Waste Management states that waste management needs to be carried out in a comprehensive and integrated manner from upstream to downstream in order to have a positive impact on the economy, public health, and the environment. Garbage has become a big issue on a national scale without good rules and guidelines. The purpose of this study is to provide SOPs in a circular economy with a service science perspective as a growth strategy for NYAMPIH, a waste logistics management start-up. The object of research is food and beverage businesses in Bandung, such as coffee shops, restaurants, and hotels. This study uses a qualitative approach by observing and interviewing a total of 8 respondents who have the position of manager and business cleaning division. The primary data used is NYAMPIH operations with company documents and literature reviews as well as summaries and thoughts from various sources to support this research. The results of this study are that the F&B sector is still experiencing difficulties in managing its waste because there are no regulations or guidelines that can be implemented properly by the industry due to the limited authority given and no responsibility given from superiors, the waste management and selection processes are not supported by infrastructure now. This research has implications for creating a circular economy scheme for organic and non-organic waste that results in more sustainable economic growth.